Comparison of the Postprandial Metabolic Fate of U-13C Stearic Acid and U-13C Oleic Acid in Postmenopausal Women. Issue 12 (December 2020) - Rodríguez-Morató, Jose; Galluccio, Jean; Dolnikowski, Gregory G.; Lichtenstein, Alice H.; Matthan, Nirupa R.
Abstract : Objective: Compare the postprandial fatty acid metabolism of isotopically labeled stearate (U- 13 C18:0) and oleate (U- 13 C18:1). Approach and Results: In conjunction with a randomized-controlled crossover trial, 6 hypercholesterolemic postmenopausal women (≥50 years; body mass index: 25.6±3.0 kg/m 2 ; LDL [low-density lipoprotein]-cholesterol ≥110 mg/dL) consumed isocaloric diets enriched in 18:0 or 18:1 (10%–15% E) for 5 weeks each. On day 1 of week 5, following a 12-hour fast, participants receive their experimental diet divided into 13 hourly meals beginning at 8 AM. U- 13 C18:0 or U- 13 C18:1 was incorporated into the 1:00 PM meal (1.0 mg/kg body weight). Serial blood and breath samples were collected over 12 hours and fasting samples at 24 and 48 hours. Plasma and lipid subfraction fatty acid profiles were assessed by gas chromatography-flame ionization detector, isotope-enrichment by liquid chromatography time-of-flight mass spectrometry, and fatty acid oxidation rate (expired 13 CO2 ) by isotope ratio mass spectrometry. Both diets resulted in similar plasma LDL-cholesterol concentrations. Kinetic curves showed that U- 13 C18:0 had a higher plasma area under the curve (66%), lower plasma clearance rate (−46%), and a lower cumulative oxidation rate (−34%) than U- 13 C18:1. Three labeled plasma metabolites of U- 13 C18:0 were detected: 13 C16:0, 13 C16:1, and 13 C18:1. No plasma metabolites of U- 13 C18:1 were detected within the study time-frame. Higher incorporation of 18:0 in cholesteryl ester and triglyceride fractions was observed on the 18:0 compared with the 18:1 diet. Conclusions: The neutrality of 18:0 on plasma LDL-cholesterol concentrations is not attributable to a single factor. Compared with 18:1, 18:0 had higher plasma area under the curve because of lower clearance and oxidation rates, underwent both a direct and a multistage conversion to 18:1, and was preferentially incorporated into cholesteryl esters and triglycerides. Abstract : Supplemental Digital Content is available in the text.